Rent Seeking and Environmental Degradation in Palm Oil Expansion in Tesso Nilo National Park - Ramadani, Floren Tika; Arin, Bunga Ramanda; Fachriza, Hilda; Ratu, Aji; Sihidi, Iradhad Taqwa Sihidi (Indonesian Journal Publisher, 2026)
This study aims to analyze rent-seeking practices in the expansion of illegal oil palm plantations and their contribution to environmental degradation in Tesso Nilo National Park (TNTN), Riau Province. A qualitative descriptive approach was employed using a document-based method. The study relied entirely on secondary data obtained from government reports, policy and regulatory documents, academic publications, civil society organization reports, and relevant media sources. Data were collected through systematic document analysis and analyzed using thematic and content analysis techniques guided by Rent-Seeking Theory to examine power relations, actor interactions, and institutional mechanisms that enable illegal land conversion.The findings reveal that environmental degradation in TNTN is structurally driven by a rent-seeking network involving state and non-state actors, including government officials, palm oil entrepreneurs, and land brokers. These actors exploit regulatory loopholes, weak law enforcement, and fragmented institutional authority to facilitate illegal land clearing and informal land legitimization. As a result, ecological damage occurs systematically, reflected in extensive deforestation, habitat loss, increased human-wildlife conflict, and weakened conservation governance. This study concludes that Environmental Degradation in TNTN is rooted in governance failure and unequal power relations rather than merely technical limitations. Therefore, structural reforms emphasizing transparency, accountability, and consistent law enforcement are essential to dismantle rent-seeking practices and ensure sustainable conservation management.